Proyecto de factibilidad para la implantación de una sucursal de la microempresa Pro-Hogar en el cantón Piñas, provincia de el Oro. - Espinoza Ordóñez, Maritza Edizabeth (2012)
This research was conducted in the Canton Piñas, Province of "El Oro", in order to contribute to socio-economic development, creating jobs for the sector, with the implementation of a branch of microenterprise "PRO- HOGAR ", dedicated to the marketing of home appliances. The province of "Gold" is an environment characterized by economically active, because it strengthens the diversity of economic activities that exist in the middle, so that the rainfall in the mountains is exploited for plantations of tropical cacao, snuff, fruit, citrus, sugarcane, especially bananas. It also allows other uses such as forestry, production of wood. In mining the gold highlights and iron. To address the issues raised the following objectives: To make a diagnosis of current situation and determining the canton microenterprise supply and existing demand, develop a technical and organizational, and carry out the financial evaluation. To develop this thesis used different methods and techniques that are the basis for finding actual and timely data, including: scientific method: to observe and explain the reality of the canton, Inductive-Deductive Method: to process getting information supply and the existing demand, Method Description, in the collection, tabulation, interpretation and analysis, Analytical Method: Determines the marketing process, project requirements, and the number of staff required to work in that branch. As the skills involved in the research work detailed as follows: Direct Observation: allows for a more complete picture as to the location of competition and marketing processes, Literature Review: Provides bibliographic information through different materials books, documents and Internet Survey: applied in a strategic sector of the canton Piñas, this is to families. The main results of the study are: location of the premises of the branch will be in the streets and Miguel Angel Suarez Sucre for being a strategic location, with adequate infrastructure and basic services such as access roads adequate; The branch of the store will a useful life of 5 years. We designed the organizational structure of the company, which will allow the proper functioning of each of the activities of staff, it takes an investment of $ 37,537.29, of which the capital shall be solved in 100% of the investment, which developed financial evaluation with different coefficients of risk assessment: The Net Present Value (NPV) is $ 30,656.05; The Internal Rate of Return (IRR) is 44.61% which is higher than the rate of commercial bank's current 15.20%, the cost benefit ratio reaches $ 1.11 indicating that for every dollar invested will get 0.11 cents of profit and capital recovery period under the conditions proposed in the project is 3 years. Finally we present the conclusions and recommendations: Analyzing the above indicators for decision-making, it is concluded that the investment project is feasible to implement, would be of great importance to the implementation of the branch, because it plays a vital role within the canton as meet existing demand, and also would encourage both social and economic development because it would hire local staff in order to contribute to the generation of jobs.